Pengalihan Tanggung Jawab Pembayaran Utang Debitur Pinjaman Online kepada Ahli Waris - Audina Rahma; Diah Gayatri Sudibya; I Nyoman Putu Budiartha (Jurnal Preferensi Hukum, 2022)
Fintech Lending or Online Loans is an electronic media-based financial loan service that facilitates lenders and loan recipients through an application or website. All financial transactions are carried out under Electronic Contracts. Often the Online Loan Contract does not include a clause regarding the risks that may occur if the loan recipient (debtor) dies before the loan (receivable) is paid off. The problems in this study is the validity of the online loan agreement and the transfer of responsibility for paying debts from online loan debtors to their heirs. This study applies a normative method with a statutory and conceptual approach. The conclusion of this study is that the recipient of the loan/debtor is obliged to repay the money borrowed to the lender/creditor according to the amount and the agreed time period. The heirs can be held responsible for paying off debts when the heirs have stated that they have received the inheritance as referred to in Article 1045 of the Civil Code.